Analisis Penyanggaan Berdasarkan Karakteristik Batuan Pada Atap dan Dinding Lubang Tambang Batubara Bawah Tanah BMK-04 di CV. Bara Mitra Kencana, Kecamatan Talawi, Sawahlunto - Wahyu Eko Prasetianto; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2018)
Physical properties and mechanical properties of rocks will be needed for analyzed RMR-Bieniawski 1989. The data will then be needed for supporting calculations (Biron and Arioglu theory, 1983). Based on the results of soil mechanical laboratory test and rock mechanics obtained values of physical properties for claystone is an average water content value 3.46%, the average spesific grafity 2.42, and average density 1.54 grams/cm3. For sandstone the natural density 2.55 gr/cm3, the dry density 2.53 gr/cm3, the saturated density 2,69 gr/cm3, apperent SG 2,53, true SG 3, natural water content 0.73%, saturated water content 6.15%, degree of saturation of 11.93%, porosity 15.56%, and void ratio 0.18. For marlstone we get the natural density 2,83 gr/cm3, the dry density 2,77 gr/cm3, the saturated density 2,88 gr/cm3, apperent SG 2,77, true SG 3,14, natural water content 1.94%, saturated water content 3,86%, degree of saturation 57,09%, porosity 10,99%, and void ratio 0,13. For mechanical properties such as, compressive strength of claystone 1,25 MPa, sandstone 3,64 MPa, and marlstone 5,48 MPa. From the results of the Bieniawski-1989 RMR analysis, the rocks on the roof and wall tunnel BMK-04 has a value of RMR 56 and include to rock class III. RMR 56 have span value and stand up time 1 week to 5 m span. Based on the analysis using Biron and Arioglu theory in 1983 obtained the value of stress to the cap of 414.01 Kg/cm2, side post 369.91 Kg/cm2, and the distance between wedges of 5,52 cm.Keywords: Ground Support, Geotechnical, Rock characteristhics, Rock Mass properties (RMR-System),  Underground mining.